Analisis Hukum Islam Terhadap Penundaan Kehamilan Dalam Praktek Perkawinan Muslim ( Birth Control ) - JUAN DINI (Edulaw : Journal of Islamic Law and Yurisprudance, 2026)
This study aims to examine birth control in the context of Muslim marriage from the perspective of Islamic law, with a primary focus on the aspects of permissibility and sharia restrictions. This study explains that family planning programs are, in principle, in line with the objectives of Sharia if they are directed towards achieving benefits, such as maintaining the health of mothers, regulating birth spacing, and improving family welfare, and are carried out through temporary contraceptive methods that do not permanently damage reproductive functions. However, some Muslims view this practice as contrary to the objectives of marriage and Sharia teachings. By applying a normative approach based on the Qur'an, hadith, and the views of classical and contemporary scholars, this study concludes that the legal status of KB can vary from permissible, recommended, obligatory, disliked, or forbidden, depending on the motive and method used. Therefore, family planning can be justified if it is based on health and welfare reasons, agreed upon by both husband and wife, and does not aim to reject the gift of offspring, while permanent sterilization and practices that lead to the complete elimination of offspring are considered incompatible with the purpose of marriage in Islam.